HORVÁTORSZÁG HÉT ÉVE AZ EURÓPAI UNIÓBAN - Bencze, Edit Lőrinczné dr. (Közép-Európai Közlemények, 2020)
Today, when Croatia has been a member of the EU for seven years, there are a variety of issues that have to be considered in the context of what Croatian accession to EU means to Croatia, i.e. what changes it caused and how it contributed to its development. The aim of the essay is to introduce Croatian interest representation in the EU and analyse the impact of the accession process on the development of the Croatian political and economic system, as well as its impact on the sociocultural changes in society and the perception of the EU among Croatian citizens. To sum up, the experience of the first years of Croatia’s membership in the EU sends some clear message to the candidate countries, namely not all benefits are evident in the short run but deepest changes can already be noticed in the transformed society and institutions. The EU membership will not generate growth itself - economic progress depends on Croatia’s own efficiency to carry on reforms.